The Utilization Potential of Tasikamdu Star Fruit Composted Waste for Mustard Cultivation (Brassica rapa L.) In Supporting Sustainable Agriculture - Yadarabullah; Sumiasih, Inanpi Hidayati; Puspitawati, Mutiara Dewi; Maulana, Fayyadh Yusuf (International Journal of Applied Biology, 2023)
Attaqie Farm Agroedutourism produced 1.5 tons/ha of star fruit waste in 2018, which was wasted because it was not utilized by starfruit farmers. Attaqie farm strives to implement the Sustainable Agriculture System (SPT) to support sustainable agriculture. The waste originating from one cultivation can be used as a resource in other forms. The application of integrated and sustainable agriculture is beneficial for farmers to preserve the ecology while maintaining the culture adopted in an area. Farmers' objectives for agricultural cultivation are good, healthy, and maximum yields, therefore the availability of compost is needed. The technology that has developed makes it easier for farmers or researchers to make compost in a short time. The study began with making compost with star fruit waste, namely residual leaves and fruit from thinning. This research was carried out using a Randomized Block Design (RBD). The treatment was replicated 4 times, with 3 experimental units, and 5 dose levels. Nutrients in the star fruit waste compost showed good results for compost criteria according to SNI 19-7030-2004 standard. The effective dosage for star fruit compost in mustard cultivation was 20 tons/ha (equivalent to 40 g/polybag).